Virtual Reality Methods A Guide for Researchers in the Social Sciences and Humanities - Jones, Phil (Policy Press, 2022)
ePDF and ePUB available Open Access under CC-BY-NC-ND licence. Since the mid-2010s, virtual reality (VR) technology has advanced rapidly. This book explores the many opportunities that VR can offer for humanities and social sciences researchers. The book provides a user-friendly, non-technical methods guide to using ready-made VR content and 360° video as well as creating custom materials. It examines the advantages and disadvantages of different approaches to using VR, providing helpful, real-world examples of how researchers have used the technology.